2015
DOI: 10.1016/j.neulet.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of Casein kinase 2 in hepatitis C NS5A-mediated inhibition of Kv2.1 K + channel function

Abstract: Inhibiting injury-induced increases in outward K +currents is sufficient to block cell death in cortical neuronal injury models. It is now known that apoptosis is facilitated in hepatocytes by the same K+ channel as in cortical neurons, namely the delayed rectifier K+ channel Kv2.1. The hepatitis C virus (HCV) protein NS5A prevents the apoptosis-enabling loss of intracellular potassium by inhibiting Kv2.1 function and thus blocking hepatocyte cell death. Critically, neurons expressing NS5A1b (from HCV genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Finally, we observed very similar channel voltage activation profiles in all of the experimental groups ( Fig. 2D), suggesting that 1) the observed changes in Kv2.1 function following TBOA exposure are distinct from other forms of channel modulation not directly related to cell death (Mohapatra et al, 2007); and 2) NS5A expression, as reported previously (Norris et al, 2012;Clemens et al, 2015), does not substantially affect normal channel function. The half-maximal activation voltages for all experimental groups were as follows: vector/vehicle, 21.09 6 2.79 mV (n 5 12); vector/T-BOA, 14.58 6 1.26 mV (n 5 12); NS5A/vehicle, 20.14 6 2.57 mV (n 5 12); and NS5A/TBOA 18.78 6 2.80 mV (n 5 10).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, we observed very similar channel voltage activation profiles in all of the experimental groups ( Fig. 2D), suggesting that 1) the observed changes in Kv2.1 function following TBOA exposure are distinct from other forms of channel modulation not directly related to cell death (Mohapatra et al, 2007); and 2) NS5A expression, as reported previously (Norris et al, 2012;Clemens et al, 2015), does not substantially affect normal channel function. The half-maximal activation voltages for all experimental groups were as follows: vector/vehicle, 21.09 6 2.79 mV (n 5 12); vector/T-BOA, 14.58 6 1.26 mV (n 5 12); NS5A/vehicle, 20.14 6 2.57 mV (n 5 12); and NS5A/TBOA 18.78 6 2.80 mV (n 5 10).…”
Section: Resultssupporting
confidence: 82%
“…It is worth noting at this point that NS5A is also the site of action of ledipasvir, a principal component of a highly successful HCV antiviral drug (Pawlotsky, 2013). We found, however, that the presence of ledipasvir does not influence the activity of NS5A on the Kv2.1 channel, suggesting that other components of the viral protein are critical for K 1 channel inhibition (Clemens et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
“…Subsequently, the NS5A-D2 was in vitro phosphorylated by CKII ( Fig. 1 ) [8] , [9] , [10] , [11] . The resulting NS5A-D2_CKII sample was then analyzed by circular dichroism spectroscopy ( Fig.…”
Section: Datamentioning
confidence: 99%
“…So far, no precise molecular function has been identified for this viral protein (Ross-Thriepland and Harris, 2015) [6] which is required for viral replication (Tellinghuisen et al, 2008) [7] . In this article, we present datasets of NMR and circular dichroism analyses of the domain 2 of the HCV NS5A protein (NS5A-D2) phosphorylated in vitro by the Casein Kinase II (CKII) (Dal Pero et al, 2007; Clemens et al, 2015; Masak et al, 2014; Kim et al, 2014) [8] , [9] , [10] , [11] . We describe the in vitro phosphorylation of the serine 288 (pS288) of NS5A-D2 by CKII and report the circular dichroism spectrum of the phosphorylated domain (NS5-D2_CKII).…”
mentioning
confidence: 99%